Belgium : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
This 2011 Article IV Consultation reports that the vulnerability of Belgium's sovereign debt to market pressures makes credible medium-term fiscal consolidation a priority. The 2012 budget includes sizable consolidation measures, and the government is committed to take additional measures as needed with the aim of reaching structural balance by 2015. In light of the weak growth prospects, automatic stabilizers should be allowed to operate freely around the consolidation path. There is a need to strengthen banking supervision and to implement the Basel III and Solvency II regulatory frameworks.